Analisis Evapotranspirasi Menggunakan Metode Penman-Monteith pada Vertical Garden - Arifin Daud; Citra Indriyati; Sarah Yuli Hasanah (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2021)
The development of environmentally friendly infrastructure is very important to reduce the environmental damage that has occurred. Environmentally friendly infrastructure can be supported by vertical garden. Plants in vertical garden undergo evaporation process called evapotranspiration process. The evapotranspiration process can be used to find out the needs of water in plants. The method used to obtain the evapotranspiration value is the Penman-Monteith method. The plants used are Plectranthus scutellarioides, Begonia, Coleus, Euodia ridleyi dwarf, Euodia ridleyi, and Chlorophytum comosum. The reference evapotranspiration value in The Hydraulic Laboratory of Sriwijaya University is 4.9826 mm/day and the smallest is 2.1262 mm/day. The reference evapotranspiration value is influenced by temperature, wind speed, and humidity conditions. Based on these three influences, temperature has a greater influence on the reference evapotranspiration. The largest evapotranspiration value of the six types of plants used is the Plectranthus scutellarioides, which is 3.3347 mm/day, the evapotranspiration value of the smallest plant is Euodia ridleyi dwarf, which is 2.6616 mm/day. The location and arrangement of plants and environmental conditions such as temperature, humidity, wind speed affect the amount of evapotranspiration value.